Carvings on the parapet wall - sequences from Mahabharata - Krishna's killing of various demons; Below the parapet wall - carved miniatures temple towers - Brig. Ajai Singh (2021)
[ Image courtesy: Brig A.P. Singh - www.collectingmoments.in ]